Semiotic Analysis at Javanese Traditional Events in West Maredan, Tualang District, Siak Regency - Tri Ardya Pramesti; Muhammad Mukhlis (Pelopor Publikasi Akademika, 2023)
This study aims to determine the denotative meaning, connotative meaning, and symbolic meaning contained in Javanese traditional events in Maredan Barat, Tualang District, Siak Regency. The source of data in this study is a Javanese traditional event in Maredan Barat, Tualang District, Siak Regency which includes qualitative data such as writing words and sentences in the traditional event. The method in this study uses descriptive analysis. The method used in this research is ethnographic research method. Data collection techniques with observation, documentation, interviews, note-taking techniques, and recording techniques. The data obtained at the Javanese Traditional Event in Maredan Barat, Tualang District, Siak Regency amounted to 8 data and were analyzed based on the problems studied. Semiotics data analysis on Javanese Customary Events in West Maredan, Tualang District, Siak Regency is divided into (1) denotative meaning, (2) connotative meaning; and (3) symbolic meaning. The analysis of the three meanings was carried out in Javanese traditional ceremonies, namely: (1) Temu manten, (2) Throwing Betel, (3) Stepping on the Egg, (4) Carrying Manten, (5) Kacar-kucur, (6) Dulangan, and ( 7) Sungkeman